2020
DOI: 10.1002/ange.202007767
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Geometric Site Dependence of Spinel Oxides for the Electrooxidation of 5‐Hydroxymethylfurfural

Abstract: Co-based spinel oxides,which are of mixing valences with the presence of both Co 2+ and Co 3+ at different atom locations,are considered as promising catalysts for the electrochemical oxidation of 5-hydroxymethylfurfural (HMF). Identifying the role of each atom site in the electroxidation of HMF is critical to design the advanced electrocatalysts.Inthis work, we found that Co 2+ Td in Co 3 O 4 is capable of chemical adsorption for acidic organic molecules,a nd Co 3+ Oh play ad ecisive role in HMF oxidation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Lu et al. studied the electrochemical performance in the oxidation of HMF over cobalt spinel oxides (Co 3 O 4 , ZnCo 2 O 4 , and CoAl 2 O 4 ) by constructing specified blocks in the tetrahedral sites (CO 2+ Td ) and octahedral sites (CO 3+ Oh ) to reveal the geometric site‐dependence of electrocatalytic oxidation of HMF [48] . The electrochemical performance was as follows: CoAl 2 O 4 < ZnCo 2 O 4 < Co 3 O 4 , which showed that octahedral CoO 6 had high catalytic activity.…”
Section: Electrocatalytic Conversion Of Hmfmentioning
confidence: 99%
“…Lu et al. studied the electrochemical performance in the oxidation of HMF over cobalt spinel oxides (Co 3 O 4 , ZnCo 2 O 4 , and CoAl 2 O 4 ) by constructing specified blocks in the tetrahedral sites (CO 2+ Td ) and octahedral sites (CO 3+ Oh ) to reveal the geometric site‐dependence of electrocatalytic oxidation of HMF [48] . The electrochemical performance was as follows: CoAl 2 O 4 < ZnCo 2 O 4 < Co 3 O 4 , which showed that octahedral CoO 6 had high catalytic activity.…”
Section: Electrocatalytic Conversion Of Hmfmentioning
confidence: 99%
“…42 The low-frequency region (10 -1 Hz-10 1 Hz) is related to the nonhomogeneous charge distribution, namely the appearance of oxidation species at the electrode interface. 10 In Fig. 4a and Supplementary Fig.…”
Section: The Electrochemical Performance Ofmentioning
confidence: 99%
“…7, 8, 9 2,5-furandicarboxylic acid (FDCA), as a typical product of the HMF conversion, is an essential monomer for the production of poly (ethylene 2,5-furandicarboxylate) to replace petroleumbased polyethylene terephthalate. 10,11 HMF electrocatalytic oxidation (HMFOR) is a promising approach to realize a high yield of FDCA at ambient temperature and pressure. 12,13,14 The adsorption/desorption behavior is regarded as a critical step in the catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…The current strategies to boost the transformation of speci c substrates mainly rely on the involvement of functional additives 11 (e.g., organic ligands, bases and mediators), a high work potential and/or sacri cial transition metal electrodes 18 , which all will severely limit real-industry applications. Principally, the preparation of cost-effective and active electrode materials is at least as important as the development of a new methodology for selective C−H bonds activation [19][20][21][22][23][24][25][26] , and only non-targeted, commercial rst generation electrodes (such as carbon rod, platinum and reticulated vitreous carbon) are applied as the current collectors in electrochemical organic synthesis at the moment. The signi cant progress reported using well-designed reaction-speci ed electrodes in improving the catalytic activity for water splitting, nitrogen reduction reactions and even carbon dioxide reduction reactions [27][28][29][30] further manifests the huge gap between the design of novel electrode materials and the requirements of sustainable electrochemical organic synthesis.…”
Section: Introductionmentioning
confidence: 99%